A Deep Dive into Duck Farming: Assessing Current Conditions, Procedures, and Technological Advances - Karthikeyan MP, Megha Pandeya, Prabha Shreeraj Nair (Revista Electronica de Veterinaria, 2024)
This comprehensive study of duck farming includes the kind of ducks that work effectively for the industry, the challenges of housing them, environmental considerations and the use of technological advances. To understand the social and economic environment in which duck farmers operate, the study stresses the relevance of demographic variables. The study concludes by shedding light on key demographic traits and offering a rich socioeconomic mosaic of groups involved in duck farming using statistics from two districts. It details duck house design and management, highlighting the need for water supply, environmental considerations and disease control. Part of the paper emphasizes managing ducklings and adult ducks, focusing on the significance of nutrition, health and breeding methods. The research examine at how well duck farms are technically run by looking at the factors that affect productivity metrics using Maximum Likelihood Estimates. We take a seven-week examination of the growth trends of many duck breeds to help improve feed scheduling and farm management in general. This research provides an integrated perspective of duck farming, illuminating the industry in general and offering practical suggestions for improving its sustainability and efficiency.